New species group and two new species of the genus Hesperus from China (Coleoptera: Staphylinidae: Philonthina) - Cai, Yu-Jie; Li, Yue-Yang; Tang, Liang (Zootaxa, 2024)
A new species group, Hesperus babai group, is proposed based on characters of the subserrate antennae and apical portion of median lobe hatchet-like, along with description of a new species: H. pengi sp. n. (Hainan). A new species of the Hesperus borneensis group is described: H. flexibilis sp. n. (Xizang). Hesperus birmanus Cameron, 1932 is newly recorded from China (Yunnan, Hainan). Habitus and diagnostic characteristics of all mentioned species are provided. A key to Chinese species of the borneensis group and babai group are also provided.